A query language for WordNet-like lexical databases. (2016) - Kubis, Marek
WordNet-like lexical databases are used in many natural language processing tasks, such as word sense disambiguation, information extraction and sentiment analysis. The paper discusses the problem of querying such databases. The types of queries specific to WordNet-like databases are analysed and previous approaches that were undertaken to query wordnets are discussed. A query language which incorporates data types and syntactic constructs based on concepts that form the core of a WordNet-like database (synsets, word senses, semantic relations, etc.) is proposed as a new solution to the problem of querying wordnets.